The role of artificial intelligence in the relationship between leadership skills and crisis management to improve business continuity of electricity and water office in Ajman, United Arab Emirates - Alblooshi, Moosa Ahmed Jafar Almandoos (2023)
The aim of this study is to investigate the role of artificial intelligence in the relationship between leadership skills and crisis management to improve business continuity at the Federal Electricity and Water Authority in Ajman. This survey was conducted using the stratified random sampling method to select 345 people who work for the Federal Electricity and Water Authority in Ajman. Data was collected through a questionnaire prepared by the researcher, which included crisis management, leadership skills, business continuity, and artificial intelligence. The SPSS 23 software was used to analyze the collected data. The results showed that there is statistically significant relationship between leadership skills and crisis management, and that there is a statistically significant relationship between artificial intelligence and crisis management. Moreover, there is a significant relationship between artificial intelligence on leadership skills, and the existence of a statistically significant relationship between leadership skills on business continuity, and the existence of a statistically significant relationship between crisis management on the authority's business continuity. This shows that artificial intelligence affects business continuity in a substantial and significant way. Artificial intelligence is found to be a partial mediator between leadership skills and crisis management. The study recommended the conduct of similar studies in other institutions in the UAE.